Factors Affecting the Metamodelling Acceptance: A Case Study From Software Development Companies in Malaysia - Mezhuyev, Vitaliy; Al-Emran, Mostafa; Murni, Fatehah; Ng, Chin Hong (IEEE, 2018)
Metamodeling has become a crucial technique in the process of software development. However, the level of metamodeling acceptance is still very low in software development companies. To the best of our knowledge, this paper can be considered as the first that aims to examine the factors that affect the metamodeling acceptance by software engineers. To achieve this aim, the technology acceptance model was adopted and extended by adding additional factors, which are the organizational and team-based factor, perceived maturity, and perceived effectiveness. Data were collected from 152 software engineers from different software development companies in Malaysia. SmartPLS was used to conduct the partial least squares-structural equation modeling (PLS-SEM) for assessing the measurement and structural models. The results indicated that perceived usefulness, perceived ease of use, organizational and team-based factor, perceived maturity, and perceived effectiveness have a significant impact on metamodeling acceptance. The R2 was 0.887 for metamodeling acceptance, which indicates that the level of model prediction is relatively substantial. Limitations and prospects for future research are also discussed.